Nature’s impact on human health and wellbeing: the scale matters - Zerbe, Stefan; Schmid, Hannah-Lea; Hornberg, Claudia; Freymüller, Julius; Mc Call, Timothy (Frontiers in Public Health, 2025)
Contact with nature can have a significant influence on human physical and mental health and wellbeing. As such, various concepts and theories as well as therapeutic approaches have been developed. The term “nature,” however, covers a broad range of size and scales, ranging from individuals or small groups of animals or plants, certain ecosystems toward landscapes. The purpose of this paper is to differentiate concepts, theories, and therapy forms according to the scales of nature. We base our conceptional approach on the biological/ecological scales of species/individuals, ecosystems/land-use types, and landscapes. Based on a review, we differentiate the current state of the utilization of greenspace exposure measurements and measures assessing mental health according to these scales. We argue that a clear differentiation of biological and ecological scales provides a better understanding of the impact of nature with its components, characteristics, and dynamics on human health and wellbeing. Our paper also supports further inter- and transdisciplinary research as well as methodological approaches with regard to environment and health, such as environmental public health.